2022
DOI: 10.1590/0004-282x-anp-2021-0065
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation in patients with cerebellar ataxias

Abstract: Cerebellar ataxias comprise a heterogeneous group of diseases characterized by motor and non-motor symptoms, which can be acquired, degenerative, or have a genetic cause, such as spinocerebellar ataxias (SCA). Usually, the genetic and neurodegenerative forms of cerebellar ataxias present a progressive and inevitable worsening of the clinical picture so that rehabilitation treatment is fundamental. Rehabilitation treatment includes physical therapy, respiratory therapy, speech, voice and swallowing therapy, occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…There is no effective treatment and current treatment strategies are based on rehabilitation therapies, including special strength and balance training to increase stability as well as compensatory strategies (25). In the next decade, novel treatments might target in pathogenesis, including mitochondrial dysfunction, impaired DNA repair, by modulation of gene expression, stem cell transplantation, gene transfer, or interventions in viral pathways (26).…”
Section: Discussionmentioning
confidence: 99%
“…There is no effective treatment and current treatment strategies are based on rehabilitation therapies, including special strength and balance training to increase stability as well as compensatory strategies (25). In the next decade, novel treatments might target in pathogenesis, including mitochondrial dysfunction, impaired DNA repair, by modulation of gene expression, stem cell transplantation, gene transfer, or interventions in viral pathways (26).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a systematic review stated balance exercises, coordination training, aerobic exercises like cycling, gait training, range of motion, and strengthening exercises for the extremities or a combination of these exercises for such patients [ 10 ]. These exercises also facilitate motor performance and diminish ataxia symptoms, enabling patients to accomplish personally significant daily goals [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the improvement in lower limb muscle activation in CA patients is typically characterized as a positive change in patterns of muscle recruitment and coordination during movement (Mari et al, 2014). Improved muscle activation indicates that (Peri et al, 2019;Chien et al, 2022) such as CAREN may focus on improving this coordination to achieve smoother and more controlled lower limb movements. In addition, CA patients often develop compensatory strategies to maintain balance.…”
Section: Emgmentioning
confidence: 99%
“…Physiotherapy is the main treatment for gait and balance alterations for CA patients, although few authors have reported its effectiveness ( Chien et al, 2022 ). Promising conventional rehabilitation approaches include dynamic balance training, customized interventions targeting balance and independence in activities of daily living, the Bobath approach, and personalised gait training ( Kelly and Shanley, 2016 ; Yap et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%